Pemetaan Kapabilitas Kantor Wilayah Bank Syariah Indonesia Region Jakarta (Periode 2020 - 2022) - Savitri, Siska; Buono, Agus; Suprayitno, Gendut (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2023)
The banking industry is required to accelerate the implementation of digital banking in order to be able to compete in order to provide services that are easier and faster and in accordance with customer needs. banking is one of the important pillars as an intermediary for the community to build small medium and micro industries and the role of banking is very important in building the country's economy in the digital era. Small and Medium Industry players must start transforming to digitalization, by changing transactions that were previously traditional into digital financial transactions. The purpose of this research is in DKI Jakarta. This study aims to identify the resources and capabilities of the Bank Syariah Indonesia (BSI) Jakarta region which have the potential to become a sustainable competitive advantage. This study uses primary and secondary data. Primary data was obtained from distributing questionnaires to respondents and interviewing experts (upper and middle management of BSI Jakarta area) using in-depth interviews. Secondary data obtained from literature studies. Based on the results of the discussion that has been described, it can be concluded that there are as many as 30 variables in the resources and capabilities of the BSI Jakarta region that have the potential to become a competitive advantage. The results of the VRIO analysis show that there are 14 variables in the resources and capabilities of the BSI Jakarta region which have a sustainable competitive advantage. Apart from that, good human resource services should be maintained and their capabilities improved so that they can educate the Small and Medium Industries in using the digital banking system contained in BSI in the Jakarta region which is the backbone for growth both in terms of assets, third party funds and financing for BSI. BSI Jakarta region needs to have an operational strategy in order to be able to carry out the main strategy that is the focus of BSI, one of which is strengthening capacity and capability and developing Small and Medium Industries. The business strategy for the BSI Jakarta region in supporting BSI strategy can be formulated from the resources and capabilities of BSI.